Mosby's dictionary of medicine, nursing & health professions. - Mosby, Inc. (St. Louis, Missouri : Elsevier, 2017)
"Regarded as one of the most respected and widely used health professions references, this all-inclusive dictionary helps you make sense of the complex world of health care. It includes detailed entries that give you the knowledge needed to communicate effectively with colleagues in various disciplines and is an indispensable guide to use throughout your career"--Page 4 of cover.
Includes bibliographical references.
Keywords: Medicine -- Dictionaries; Nursing -- Dictionaries; Medicine; Nursing; Allied Health Occupations; Medicine; Nursing; Dictionary; Dictionaries